The Impact of Telecom Infrastructure on the Economic Growth: The Case of Oil-producing and Non-Oil Producing Arab Countries - Matalqah, Mamoun Mohamad; Warad, Talib Mohamad (International Journal of Economics and Financial Issues, 2017)
This study attempts to assess the impact of investment in the infrastructure of the telecommunications sector on economic growth in the Arab countries, using advanced econometric techniques, such as fully modified ordinary least squares, and panel data analysis utilizing cross sectional data covering 12 countries and a period of 20 years 1996-2015. The study finds evidence that investment in infrastructure for the telecommunications sector has a positive and significant effect on economic growth in non-oil producing countries in the long-term; it shows that a 10% increase in the number of telecom subscribers leads to an increase of 3% in real gross domestic product in these countries. The results also show that there is no impact for telecommunication on the economic growth of oil-producing countries. In light of the above findings, policy makers should pay more attention to the telecom sector in the Arab countries, and encourage investment in this sector. Keywords: Telecom Infrastructure, Economic Growth, Fully Modified Ordinary Least Squares, Oil Countries, Co-integration, Arab Countries JEL Classification: O12